Oral Health Problem in Indonesia: An Ecological Analysis - Titis Maulanti; Muji Sulistyowati; AgungDwi Laksono (Indian Journal of Forensic Medicine & Toxicology, 2021)
Oral health problem needs special attention around worldwide, including in Indonesia. This study analyzedfactors related to oral health problems, including tooth-brushing behavior, dental visit, and public healthcenters with many dentistsin all provinces in Indonesia. In this study, the ecological approach was carriedoutusing secondary data from the Ministry of Health of the Republic of Indonesia in 2018.Data from 34provinces in Indonesia regarding tooth brushing behavior, dental visit, and public health centers with asufficient number of dentistswere analyzed against the proportion of oral health problems using crosstabulation.This study found that the ratio of oral health problems in Indonesia is in the moderate categoryandtooth brushing behavior, dental visit, and public health centers with many dentistsin all provinces. Thus,oral health promotion and preventionthrough increasing awareness of maintaining oral health and equaldistribution of dentists must be carried out to establish healthy community behavior in all provinces inIndonesia.